SISTEM PENGAMANAN SISTEM INFORMASI RAWAT JALAN DI KLINIK - Angga Wiranata; Ade Wiradito; Muhammad Reza Ardhana; Triase (Jurnal Informatika Teknologi dan Sains (Jinteks), 2023)
Outpatient Information System is a critical system that concerns a person's life. In maintaining the security of patient data to keep it safe, efforts need to be made to avoid threats that can disrupt the running of the system. This study aims to determine threats to data security in outpatient information systems. This research uses a literature study method that uses a purposive sampling technique that uses journals so that it produces discussions and also conclusions in this study. Data security and confidentiality are important issues. Cases related to data security become a job that requires substantial handling costs. So that it can be concluded that the security of data on patients can be known by those criminals who steal patient data at the clinic.